Education, training and economic performance: Evidence from establishment survival data - William Collier; Francis Green; Young-Bae Kim; John Peirson (University of Kent, Department of Economics, 2008)
We consider the links between training, the quality of labour and establishment performance, using a proxy for performance, commercial survival. We develop a model in which managers have varying beliefs about the efficacy of education and training, leading to potential variation in the optimal provision of education and training. Between 1998 and 2004, 16% of private sector establishments in Britain with at least 5 employees closed down. Our principal new findings are, first, that establishments which train at least some experienced employees in the largest occupational group are 13 percentage points more likely to survive; second, that establishments are more likely to survive if they employ more educated labour; third, however, among establishments that do train, the survival prospects are not altered by the duration of training per employee. We infer from these findings that government policy aimed at encouraging more employer-sponsored training without deploying regulation or subsidy should focus on employers that do not train at all.
Keywords: J24; J51; L21; 330; training; education; human capital; profit; skill; Unternehmensentwicklung; Wirtschaftskrise; Humankapital; Arbeitskräfte; Qualifikation; Betriebliches Bildungsmanagement; Großbritannien